Ni-PI-Ni based nanoarchitectonics near-perfect metamaterial absorber with incident angle stability for visible and near-infrared applications - Abu Hanif; Touhidul Alam; Mohammad Tariqul Islam; Mohammad Lutful Hakim; Iskandar Yahya; Saleh Albadran; Md. Shabiul Islam; Mohamed S. Soliman (International Journal of Optomechatronics, 2024)
This article presents a wideband metamaterial absorber (WMMA) for the visible and near-infrared (NIR) region application. The proposed metamaterial absorber comprises three layers of sandwiched (metal-dielectric-metal) model based on Nickel-Polyamide-Nickel. The multiple resonators on top layers achieve an average absorption of 98.16% over a range from 380 to 2300 nm with a compact unit cell size of 100 × 100 × 42 nm3. The designed WMMA shows 99% perfect absorption for a large bandwidth of 685 nm. Considering its wideband absorption, the physical absorption phenomenon was also explained in terms of the proposed WMMA's surface electric field, magnetic field, and current distribution. Also, the effects of materials and structural parameters on absorption performance with a FOM have been studied. The absorption performance is analysed with various polarization angles to demonstrate polarization insensitivity. The designed WMMA shows the absorption of >70% at large incident angles of 70°. The perceptible contribution of this WMMA is large unity absorption bandwidth at visible to NIR region with high incident angle stability, polarisation insensitivity, thermal robustness of the constituting metal and simple nanostructure geometry. Therefore, the proposed WMMA has good potential in sensors, thermal emitters, photodetectors, and absorber applications.